(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
Polyaniline (PANI)/montmorillonite (MMT) composites were prepared by in-situ polymerization of aniline in the presence of MMT with ammonium persulfate (APS) and hydrochloric acid (HCl) as oxidant and acid dopant, respectively. PANI/MMT composites on structural properties were analyzed by FT-IR, XRD and SEM. The result of FT-IR analysis signified an interaction between PANI backbones and MMT layer surfaces. X-ray diffraction showed an increase in the interlayer spacing of MMT, signifying PANI was intercalated into the MMT galleries. PANI prepared in the presence of MMT exhibited flake-like morphology rather than granular particle form of PANI without MMT. PANI/MMT10% showed higher electrical conductivity than pristine PANI. PANI and PANI/MMT were separately used as the fillers to prepare paraffin composites and PANI/MMT10% had a better microwave absorbing performance than PANI. The minimum reflection loss of PANI/MMT10%/paraffin composites with thickness of 8.0 mm were -37 dB at 14.8 GHz and the effective absorption band under -10 dB was from 13 to 16 GHz.